ADAT PERKAWINAN MASYARAKAT DESA KAMPUNG TENGAH KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Fitri, Wahyuni; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This thesis is proposed to qualify for a bachelor's degree in sociology. It is titled "Adat Marriage of Kampung Tengah Village Community of Kuantan Hilir Sub-district of Kuantan Singingi Regency". This study aims to find out the functional response of the community about the marriage customs of the villages of central kampong. The marriage custom procedures in Kampung Tengah Village, namely: Introduction of a young man and a young woman, batanyo (enter the cigarette) and the last of the process of getting engaged. The engagement process involves picking up the sign, Tando tand tandus, tando tando, Manjalang fiance or samo then, Marriage or Marriage contract, Bainai, Bagholek / Kenduri, Night fetching husband, Mintuo bitch (visiting in-laws). The theory used in this research is the theory of social and functional change (parson) which includes into: Adaptation (A), Goal Attainment (G), Integration (I), and Latent Pattern Maintenance (L). Technique data collection used is interview and analyze data qualitatively. The result of this research is the functional response of Village Tengah village community to the tradition or custom of marriage that is better and happy with the marriage custom which is now because the first marriage lawfulness adoption now replaced by penghulu.Keywords: Marriage, Functional Response, Customary Marriage